The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.17221/15/2010-rae
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of different moisture contents of Jatropha curcas L. seeds under compression loading

Abstract: A study was conducted to investigate the behaviour of different moisture contents of Jatropha curcas L. seeds under compression loading. To obtain jatropha seeds of different moisture contents ranging from 1% (w.b.) to 37% (w.b.), the seeds were soaked in water and kept in a refrigerator at 5°C for different number of days. Compression devices, namely ZDM 50-2313/56/18, pressing vessel with diameter of 76 mm and a pressing plunger of 90 mm height, were used. The amount of seeds in the pressing vessel w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
5
16
0
Order By: Relevance
“…Comparing this results with previous studies on the mechanical behaviour of one seed under compression loading where unit deformation energy, rupture force and rupture compressive stress were determined, the results obtained in the present study were in agreement with the pressing of rapeseed Unal et al, 2009), jatropha seed (Karaj and Muller, 2010;Sirisomboon et al, 2007), sunflower seed (Gupta and Das, 2000;Perez et al, 2007). Also the position of oil points on the deformation characteristics of the various oilseeds corresponds to similar studies reported by (Faborode and Favier, 1996;Figueiredo et al, 2011;Sayyar et al, 2009) and also the shapes of deformation characteristic are significant to the characteristics described by (Gupta and Das, 2000;Herak et al, 2010;Kabutey et al, 2011;Rusinek et al, 2007),…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Comparing this results with previous studies on the mechanical behaviour of one seed under compression loading where unit deformation energy, rupture force and rupture compressive stress were determined, the results obtained in the present study were in agreement with the pressing of rapeseed Unal et al, 2009), jatropha seed (Karaj and Muller, 2010;Sirisomboon et al, 2007), sunflower seed (Gupta and Das, 2000;Perez et al, 2007). Also the position of oil points on the deformation characteristics of the various oilseeds corresponds to similar studies reported by (Faborode and Favier, 1996;Figueiredo et al, 2011;Sayyar et al, 2009) and also the shapes of deformation characteristic are significant to the characteristics described by (Gupta and Das, 2000;Herak et al, 2010;Kabutey et al, 2011;Rusinek et al, 2007),…”
Section: Resultssupporting
confidence: 91%
“…1, it is seen that moisture content is an important parameter which can influence the mechanical behaviour of oilseeds, that is, moisture content can cause transformation of deformation characteristic (Karaj and Muller, 2010;Sirisomboon et al, 2007;Unal et al, 2009) and thus change the maximal and limit deformation as well as deformation energy (Blahovec and Reznicek, 1980;Herak et al, 2010;Kabutey et al, 2011;Koegel et al, 1973). Porosity can also influence the mechanical behaviour of oilseeds (Fomin, 1978;Herak et al, 2011a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…fruit, nut and kernel (SIRISOMBOON et al (2007), Jathropha curcas L. seed (KABUTEY et al 2011). Despite all these studies and numerous economic values of Canarium schweinfurthii fruits, no work has been published on the post-harvest physical properties of Canarium schweinfurthii Engl.…”
Section: Methodsmentioning
confidence: 99%
“…It also saves time and money, offer ways in which products can be utilized effectively and helps to maintain quality even in adverse storage and handling conditions. Literature reveals that several studies have been carried out on engineering properties of different agricultural products; millet (Pennisetum glaucum L.) (Ndirika, Oyeleke 2006), Lablab purpureus L. (Simonyan et al 2009), Jatropha curcas L. fruit, nut and kernel (Sirisomboon et al (2007), Jathropha curcas L. seed (Kabutey et al 2011). Despite all these studies and numerous economic values of Canarium schweinfurthii fruits, no work has been published on the post-harvest physical properties of Canarium schweinfurthii Engl.…”
mentioning
confidence: 99%